Foreign Direct Investment and Economic Growth - Guido Baldi; Jakob Miethe (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
Various proposals are currently being suggested to encourage higher foreign direct investment in countries within the euro area, particularly between individual member states. The intended goal is to assist in stimulating economic growth in the euro area. Against this background, this article provides an overview of the large and heterogeneous academic literature on the influence of direct investment on economic growth. The results of the existing studies indicate that direct investment often acts as a kind of catalyst and that a positive influence on economic growth becomes more probable when a country has a population with a high level of education, high-quality infrastructure, or a developed financial system. – – Direktinvestitionen in die Länder des Euroraums zu setzen – vor allem auch zwischen den einzelnen Mitgliedsländern. Dies soll unter anderem dazu beitragen, das Wirtschaftswachstum im Euroraum zu beleben. Vor diesem Hintergrund gibt dieser Beitrag einen Überblick der umfangreichen – aber auch heterogenen – wissenschaftlichen Literatur zum Einfluss von Direktinvestitionen auf das Wirtschaftswachstum. Alles in allem deuten die Ergebnisse der bestehenden Studien darauf hin, dass Direktinvestitionen oft als eine Art Katalysator wirken und ein positiver Einfluss auf das Wirtschaftswachstum wahrscheinlicher wird, wenn ein Land über eine Bevölkerung mit einem hohen Ausbildungsstand, eine gut ausgebaute Infrastruktur oder ein entwickeltes Finanzsystem verfügt.
Keywords: 330